Psychiatry, risk and vulnerability: The significance of Robert Castel's work for nursing. (12th December 2019) - Paradis‐Gagné, Etienne; Pariseau‐Legault, Pierre
Abstract: Robert Castel is an eminent figure in the social sciences because of his innovative contributions to various social and health fields. The seminal work of this poststructuralist author and social activist has influenced several research disciplines, but has not yet had a significant impact on nursing. In this article, we will present the thinking of this man, who considered himself a sociologist, philosopher and "historian of the present." We will examine the most important issues he explored during his career, including the psychiatric apparatus, the management of risk and the social vulnerability. We believe that this thinker's perspective on diverse social issues is very relevant to nursing practice and research and to the health sciences in general. The concepts he developed and utilized with finesse provide us with a critical reading of many contemporary health issues, particularly in mental health and psychiatric nursing. Castel's critical and engaged approach incites mobilization for social justice and greater protections for marginalized and vulnerable persons. These principles of advocacy and social justice are also at the heart of the nursing profession.